Comparing traditional measures of academic success with emotional intelligence scores in nursing students - Michelle H Cheshire; Haley P Strickland; Melondie R Carter (Elsevier, 2015)
Objective: Emotional intelligence (EI) is the ability to perceive emotions, to access and generate emotions so as to assist thought, to understand emotions and emotional knowledge and to reflectively regulate emotions so as to promote emotional and intellectual growth. EI is increasingly discussed in healthcare as having a potential role in nursing. The purpose of this descriptive study was to examine the causal relationship between EI scores and the traditional academic admission criteria (GPA) and evaluation methods of a baccalaureate nursing program. Methods: The sample included second semester upper division nursing students (n = 85). EI was measured using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). Results: The results of the statistical analysis (MANOVA, ANOVA and Pearson correlational coefficient) found no significant relationships or correlations with the current methods of evaluation for admission to nursing school or the evaluation methods used once students are in the nursing program. Conclusions: These results imply that assessing a nursing student's EI is measuring a different type of intelligence than that represented by academic achievement. Based on the findings of this study and the current state of nursing education, EI abilities should be included as part of the admission criteria for nursing programs.